Molecular phylogenetic and morphological analysis of a powdery mildew found on Dalbergia lanceolaria in Thailand - Sararat Monkhung (2018)
© 2017, Chiang Mai University. All rights reserved. Phyllactinia dalbergiae and its Ovulariopsis anamorph, causing a powdery mildew fungus on Dalbergia lanceolaria, has been found for the first time in Thailand. Identification of this fungus using molecular analysis has not been previously reported. In this study, molecular phylogenetic analysis of the nuclear ribosomal DNA (28S, ITS regions including 5.8S) combined with morphology were used to clarify and confirm identification of this fungus. The phylogenetic analysis demonstrated that P. dalbergiae formed a distinct clade at the basal part of the Phyllactinia tree with 97% bootstrap support. The phylogenetic results supported the unique morphology of the P. dalbergiae anamorph that has twisted foot-cells. Additionally, the nucleotide sequences obtained from both of anamorphic and teleomorphic states were identical.